Development of improved redundancy measure for the Colorado State Highway System - Bui, Kenny, author; Jia, Gaofeng, advisor; Atadero, Rebecca, committee member; Shakouri, Mahmoud, committee member (Colorado State University. Libraries, 2022)
The Colorado Department of Transportation (CDOT) has been working to improve the resiliency of its transportation system and facilities. A vital attribute of a resilient transportation system is whether or not the system has redundancies built into it. For example, if a roadway is closed to traffic, but there are alternative routes for the drivers to take, then the closed roadway could be considered to have redundancy. The current redundancy measure that CDOT uses is based on the number of other state highways that connect to a particular highway. The redundancy measure needs refinement because it does not consider the additional travel time and distance from the alternative routes. This research aims to develop an improved method for measuring the redundancy of state highway facilities in Colorado. To establish information on the number of detours (i.e., alternative routes) for a specific road segment and the additional travel time and distance on each of the detours, detour analyses are carried out to identify (if any) the first, second, and third best alternative detours for all the highway segments in the state highway system. This is realized by closing the corresponding road segment or alternative routes, updating the transportation network, and rerunning the traffic analysis on the updated transportation network. For more accurate traffic analysis, the combined distribution and assignment model is used to take into account the effects of congestion on the traffic flow. Because the full transportation network in CDOT's state-wide model has large number of nodes and links, to reduce the computational effort for the detour analysis (which needs to be repeated for all road segments), an aggregated network based on the full network is developed and used for detour analysis for cars. Separate detour analyses are also carried out for the freight vehicles since they use a separate freight network, which is a subnetwork of the aggregated network. In the end, using the information from the detour analyses, a new improved redundancy metric is developed that takes into account not only the number of alternative routes for a road segment but also the additional time and distance on the alternative routes. The new redundancy metric also incorporates a weight for each best detour (e.g., the first, second, and third best detours are weighted differently). The detour information will be used to update the existing CDOT Detour Identification Tool. The redundancy metric can be further used to calculate and update CDOT's criticality score to determine the resiliency of the Colorado State Highway System and guide activities to enhance its resilience.
Keywords: detour analysis; redundancy measure; Colorado State Highway System; state-wide model; four-step travel model